THE TRANSFORMATION OF ISLAMIC EDUCATION THROUGH TECHNOLOGY INTEGRATION IN THE DIGITAL ERA - St. Wardah Hanafie Das; Muhammad Zaid; Muminayah; Rahmaniah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The rapid advancement of technology in the digital era has fundamentally transformed various aspects of human life, particularly in the way information is created, stored, and disseminated. In the context of Islamic education, this digital transformation presents both significant opportunities and complex challenges. This study explores the urgency of adapting Islamic education to technological progress to ensure its relevance for